Controle social: a gestão social das ações do Estado - Silva, Fernanda Rodrigues da (Universidade Federal do Tocantins, 2016)
This dissertation proposed to develop a conceptual systematization of the different scientific contributions about “Social Control”, specifically in the area of Urban and Regional Planning / Demography – PUR, in Brazil, whereof a integrative literature review, as well as to indentify the possible congruences of theoretical categories of the Social Control with the Social Management. This is a theoretical dissertation, of descriptive and exploratory purpose, developed by way of an integrative literature review. The searched databases were: SCIELO; SPELL; ANPAD and journals of the following qualifications (A1, A2, B1 and B2), classified in the evaluation area: “Urban and Regional Planning / Demography – PUR”, of the integrated application WebQualis of CAPES, 2012 version. The search on the journals was developed in the months of September and October of 2014. At the end of the searches 408 publications were found. 252 articles composed the valid sample of the integrative literature review, which were admitted in the inclusion criterions, sourced in the journals of (A1, A2, B1 and B2) qualifications, which were later submitted to a thematic categorical content analysis. The resulting categories were “Social control done by the society about itself”; “Social control done by the society about the State”; “Social control done by the State about the society”; “Social control done by the State about itself”; “Other ways of Social control”; “Does not deal with social Control aspects”. The empirical approach was the most recurrent in the evaluated publications. Toward these findings revealed a notable scarcity in theoretical studies about the social control. In the thematic analysis, were identified the Theoretical Categories of the Social Control: Democracy, Citizenship and Social Management. Through these categories was possible to certify the theoretical foundations which can delimit the concept of the Social Control. Based on the results of the theoretical conceptions about [The social control done by the society about the State], social control is the amelioration process of the deliberative democracy through the act of controlling the State actions, in public sphere, through the effective exercise of citizenship. Its range includes all channels (formals and informal) and actions attempted by the society to amplify the development of the local power and other scales, as well as to control the State performance in the public policies cycle. In this sense, the social control is ultimately the establishment of the society's control about the State's action via social management. The question that guided this dissertation was: Which are the conceptual theoretical dimensions of the studies published about the “Social Control” classified in the “Urban and Regional Planning / Demography – PUR” evaluation area and its theoretical congruences with the social management? Thus, seeking to verify, in the analyzed literature, the existence of theoretical convergences present in the relation between social control and social management which complement and approximate each other and, the answer to this search was positive, according to the aforesaid delimitation.